The Interplay Between Anxiety and Comprehension in EFL Digital Reading Contexts - ALSHEHRI, MONA (International Journal of Language and Literary Studies, 2025)
This study explores the impact of digital reading anxiety on the reading comprehension of English as a Foreign Language (EFL) learners. While it is established that reading anxiety can impede EFL learners’ comprehension—especially when using digital devices—there is limited research on this issue’s extent. To fill this gap, the study assessed 152 first-year university EFL students. Participants completed a background questionnaire, a reading comprehension test that included literal, inferential, and evaluative comprehension levels, and a digital reading anxiety scale specifically designed for EFL learners. This scale measured digital reading anxiety across seven dimensions: cognitive challenges, emotional responses, technological issues, physical discomforts, language-related anxiety, confidence, and task management. The results revealed that students generally experience moderate anxiety when reading on digital devices. Notably, students with stronger comprehension skills reported lower levels of digital reading anxiety, particularly in relation to inferential comprehension. However, no significant relationship was found between evaluative comprehension and anxiety. An independent samples t-test demonstrated that students with higher comprehension scores experienced significantly lower digital reading anxiety compared to those with lower scores. These findings provide valuable insights into the role of digital devices in EFL reading instruction and suggest that addressing anxiety may enhance reading comprehension outcomes.